1979
DOI: 10.1136/bmj.2.6195.898
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effect of co-trimoxazole on platelets.

Abstract: Summary and conclusionsDiminished survival of transfused platelets occurred in two patients given co-trimoxazole, and a third patient taking this drug developed thrombocytopenia. By means of an indirect immunofluorescence assay antibodies against donor platelets coated with co-trimoxazole were found in the sera in all cases. These antibodies were directed against the trimethoprim component of cotrimoxazole and not against sulphamethoxazole.Co-trimoxazole is a potent antimicrobial agent and is advocated for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Ackroyd 4,5,7 postulated that the drug functioned as a hapten and the binding of drug to platelet membrane rendered the drug-membrane complex antigenic. Subsequent studies by Claas and coworkers 37 were consistent with this hypothesis. These investigators used a fluorescent labeled antihuman IgG antibody and demonstrated that drugdependent antibody bound to washed platelets that had been pretreated with test drug.…”
Section: The Type Of the Interaction Between Drug Platelet And Antimentioning
confidence: 71%
“…Ackroyd 4,5,7 postulated that the drug functioned as a hapten and the binding of drug to platelet membrane rendered the drug-membrane complex antigenic. Subsequent studies by Claas and coworkers 37 were consistent with this hypothesis. These investigators used a fluorescent labeled antihuman IgG antibody and demonstrated that drugdependent antibody bound to washed platelets that had been pretreated with test drug.…”
Section: The Type Of the Interaction Between Drug Platelet And Antimentioning
confidence: 71%
“…No attempt was made in this study to determine the relative importance of fever, septicaemia and antibiotic therapy in the pathoge nesis of refractoriness because they frequently coexisted. In addition, tests were not carried out for the detection of drug-dependent platelet antibodies, which have been re ported to cause refractoriness associated with the admin istration of trimethoprim and vancomycin [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Generation of antibodies to the glycoprotein IIb/IIIa complex on platelets can cause immune thrombocytopenia, which is typically observed within the first week of treatment and is generally reversible on discontinuation of the drug. [47][48][49] Although uncommon at therapeutic doses, the inhibition of folate metabolism by trimethoprim can cause dose-related leukopenia and megaloblastosis, both of which are responsive to folinic acid. 41,42 Periodic monitoring of the complete blood count may be advisable in patients receiving a high dose of trimethoprimsulfamethoxazole for extended periods.…”
Section: O: Decreased Oxygen-carrying Capacity and Other Hematologic mentioning
confidence: 99%
“…Immune-mediated idiosyncratic reactions are often associated with a reactive metabolite, lead- [44][45][46] Hemolytic anemia Glucose-6-phosphate dehydrogenase deficiency [44][45][46] Drug-induced thrombocytopenia Antibody-mediated destruction of platelets with specificity for the glycoprotein IIb/IIIa complex [47][48][49] Cyanosis, "chocolate-coloured" blood, and falsely low oxygen saturation on pulse oximetry but a normal oxygen saturation on arterial blood gas measurement ("saturation gap")…”
Section: T: Toxic Epidermal Necrolysis and Other Hypersensitivity Reamentioning
confidence: 99%